Norm Enforcement in Social Dilemmas: An Experiment with Police Commissioners - David Dickinson; David Masclet; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2014)
Do individuals trained in law enforcement punish or reward differently from typical student subjects? We analyze norm enforcement behavior of newly appointed police commissioners in both a Voluntary Contribution Mechanism game and a Common Pool Resource game. Our experimental design includes treatments where a reward or sanction institution is exogenously imposed, as well as treatments with endogenous selection of the norm enforcement institution. Compared to a standard student-subject pool, police commissioners cooperate significantly more in both games. With exogenous institutions, police commissioners bear a higher burden of punishment costs than non-police subjects. When the norm enforcement institution is endogenous, all subjects vote more in favor of rewards over sanctions, but police subjects with some work experience are more likely to vote for sanctions. Police subjects also reward and sanction more than the others when the institution results from a majority vote.
Keywords: C92; H41; D63; 330; norm enforcement; common pool resources; voluntary contribution mechanism; police officers; experiment